Impact of Microbiota Transplant on Resistome of Gut Microbiota in Gnotobiotic Piglets and Human Subjects - Liu, Hu; Wang, Hua H. (Frontiers in Microbiology, 2020)
Microbiota transplant is becoming a popular process to restore or initiate “healthy” gut microbiota and immunity. But, the potential risks of the related practices need to be carefully evaluated. This study retrospectively examined the resistomes of donated fecal microbiota for treating intestinal disorders, vaginal microbiota of pregnant women, and infant fecal microbiota from rural and urban communities, as well as the impact of transplants on the fecal resistome of human and animal recipients. Antibiotic resistance (AR) genes were found to be abundant in all donor microbiota. An overall surge of resistomes with higher prevalence and abundance of AR genes was observed in the feces of all transplanted gnotobiotic pigs as well as in the feces of infant subjects, compared to those in donor fecal and maternal vaginal microbiota. Surprisingly, transplants using rural Amish microbiota led to more instead of less AR genes in the fecal microbiota of gnotobiotic pigs than did transplants using urban microbiota. New AR gene subtypes undetected originally also appeared in gnotobiotic pigs, in Crohn’s Disease (CD) patients after transplant, and in feces of infant subjects. The data illustrated the key role of the host gastrointestinal tract system in amplifying the ever-increasing AR gene pool, even without antibiotic exposure. The data further suggest that the current approaches of microbiota transplant can introduce significant health risk factor(s) to the recipients, and newborn human and animal hosts with naïve gut microbiota were especially susceptible. Given the illustrated public health risks of microbiota transplant, minimizing massive and unnecessary damages to gut microbiota by oral antibiotics and other gut impacting drugs becomes important. Since eliminating risk factors including AR bacteria and opportunistic pathogens directly from donor microbiota is still difficult to achieve, developing microbial cocktails with defined organisms and functions has further become an urgent need, should microbiota transplantation become necessary.